2018
DOI: 10.3892/ol.2018.8110
|View full text |Cite|
|
Sign up to set email alerts
|

miR‑148a‑3p suppresses epithelial ovarian cancer progression primarily by targeting c‑Met

Abstract: MicroRNAs (miRNAs) are a group of small non-coding RNAs that modulate post-transcriptional gene expression. It has been demonstrated that various miRNAs may be expressed at different levels in different types of tumors. The present study assessed the role of microRNA-148a-3p (miR-148a-3p) in epithelial ovarian cancer (EOC). The results demonstrated that miR-148a-3p was decreased in EOC tissues and that a lower miRa-148-3p concentration was associated with a higher overall survival rate. Transfection of miR-148… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 27 publications
4
35
0
Order By: Relevance
“…Moreover, it was shown that down‐regulation of EGFR caused by MiR‐615 and MiR‐7, led to decreased migration, and invasion of human glioblastoma and ovarian cancer cells, respectively . Analogous effect was observed following MET silencing or its down‐regulation in many cancers like ovarian cancer, breast cancer, hepatocellular cancer or gastric cancer . Corso et al also indicated that MET silencing in already established metastases led to their almost complete regression.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Moreover, it was shown that down‐regulation of EGFR caused by MiR‐615 and MiR‐7, led to decreased migration, and invasion of human glioblastoma and ovarian cancer cells, respectively . Analogous effect was observed following MET silencing or its down‐regulation in many cancers like ovarian cancer, breast cancer, hepatocellular cancer or gastric cancer . Corso et al also indicated that MET silencing in already established metastases led to their almost complete regression.…”
Section: Discussionmentioning
confidence: 94%
“…36,37 Analogous effect was observed following MET silencing or its down-regulation in many cancers like ovarian cancer, breast cancer, hepatocellular cancer or gastric cancer. 38,39 Corso et al 40 Cell migration is the multi-step process, where formation of actin-rich protrusions is needed. 42 We have previously shown that EGF and HGF stimulate invadopodia formation, and extracellular matrix degradation, what correlates with higher invasive abilities of melanoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, miR‐148a‐3p was reported to represses proliferation and EMT in bladder cancer by regulating ERBB3/AKT2/c‐myc and DNMT1 19 . miR‐148a‐3p could suppress ovarian cancer progression primarily by targeting c‐Met or suppress proliferation and invasion of esophageal cancer by targeting DNMT1 20,21 . Long noncoding RNA SNHG4/miR‐148a‐3p/c‐Met axis was reported to promote cervical cancer progression 22 .…”
Section: Discussionmentioning
confidence: 99%
“…The HGF/c-MET receptor tyrosine kinase (RTK) pathway is quiescent in normal tissue, while it is active in various tumors [ 13 ]. Growing investigations have confirmed that inhibition of HGF/c-MET signaling is an effective therapeutic strategy in suppressing multiple human cancers, such as non-small cell lung cancer (NSCLC), HCC, gastric cancer, colorectal cancer ovarian cancer, bladder cancer, head and neck cancer, cervical cancer, and some other cancers [ 4 , 7 , 8 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ]. In preclinical and clinical trials, it has demonstrated that the inhibitors of c-MET have antitumor activity in treatment of NSCLC.…”
Section: Introductionmentioning
confidence: 99%